The Provisional Government and “Chinese Question” in Russia in 1917 - Mikhail V. Khodjakov; Sun Yizhi (RUDN Journal of Russian History, 2022)
The article analyzes the changes that took place during the solution of the so-called Chinese question on the basis of the journals of the Interdepartmental Consultation under the board of the Chinese Eastern Railway, which have been preserved in the Russian State Historical Archive. The peak of activity in this direction first of the tsarist government, and then of the Provisional government was from the second half of 1916 to the autumn of 1917. Documents show that the labor of recruited Chinese workers was used in many sectors of the economy. But the most important it received in the railway construction. Russia's military operations had slowed down the colonization of the Far East. Under these conditions, the arrival of tens of thousands of Chinese workers in the European part of the country became a peculiar reflection of the eastern direction of Russia's domestic and foreign policy. The attitude toward this phenomenon in social and political circles has changed since the formation of the Provisional Government. While pursuing the course of tsarism in solving the problem of the crisis of workers' hands, the Provisional Government simultaneously made a number of concessions to the Chinese mission in Petrograd. In particular, its representatives were given the opportunity to become acquainted with the working and living conditions of the Chinese workers. Rising unemployment and protest moods in Russian society eventually forced the Provisional Government, shortly before its fall, to abandon the transportation of foreign laborers to Russia.